翻轉教學模式在「特殊幼兒教育」課程之再行動 Re-Action of the Flipped-Teaching Model in a Special Early Childhood Education Course - 黃志雄 Chih-Hsiung Huang (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2020)
本研究旨在以行動研究方式，運用翻轉教學模式於特殊幼兒教育課程中，以解決研究者在教學上所面臨之大學生課程參與和學習動機與成效的問題，同時，從教學實踐行動中，反思翻轉教學模式的運用，以及探討翻轉教學模式對學生課程參與和學習成果的影響。研究者運用之翻轉教學模式，包括課前預習、課中討論、課外專題和課後省思等四項策略，並以研究者於 2018 年所開設之「特殊幼兒教育」課程的 147 位修課學生為對象，透 過行動研究之動態循環歷程，從中反思和調整教學行動。此外，蒐集學生學習省思、教室觀察、小組學習單、同儕檢核和研究日誌等質性資料，並採用恆常比較法進行質性資料分析，同時，輔以研究者自編之學習回饋檢核表的量化資料分析，以瞭解教學實踐研究的結果。研究結果發現翻轉教學模式能有效因應和解決研究者在大學教學上所面臨的問題，同時，研究結果顯示，翻轉教學模式的實施成效包括：( 一 ) 促進學生在課堂中的參與意願、( 二 ) 增進學生對課程目標的學習，以及 ( 三 ) 提升學生在小組合作學習、自主學習、口語表達和反思等潛在課程的學習表現。本研究之翻轉教學模式和行動研究歷程，可提供大學教師在因應學生課堂參與問題，以及教學實踐探究之參考。 Adopting an action research approach, this study employs the flipped-teaching model in a special early childhood education course to deal with the problems faced by the researcher regarding undergraduate students’ course participation, learning motivation, and effectiveness. During the teaching practice, the study examined both the implementation of the flippedteaching model and its effects on student participation and learning outcomes.The flippedteaching model employed herein was comprised of four sections: pre-course preparation, classroom discussion, off-course seminar, and follow-up reflection. The participants were 147 students in a special early childhood education course taught by the researcher in 2018, and the teaching practice was reflected on and adjusted accordingly during the dynamic and cyclical process of action research. Qualitative data, including students’ reflections, records of classroom observations, group learning sheets, and research journals, were collected and then analyzed via the constant comparative method. In order to examine the outcome of teaching practice, quantitative data were also collected with a student feedback questionnaire developed by the researcher.The results include the following. (1) The flipped-teaching model can effectively raise students' willingness to participate in class and their motivation. (2) The flipped-teaching model can enhance student learning objectives in course acquisition. (3) The flipped-teaching model can promote students' performance on cooperative learning, self-learning, oral expression, and reflection.